Recurrence and survival rates of inflammatory bowel disease-associated colorectal cancer following postoperative chemotherapy: a comparative study. (8th June 2016) - Dugum, Mohannad; Lin, Jingmei; Lopez, Rocio; Estfan, Bassam; Manilich, Elena; Stocchi, Luca; Shen, Bo; Liu, Xiuli
Abstract : Background and Aim : Inflammatory bowel disease (IBD) is associated with an increased risk of colorectal cancer (CRC). Studies have shown tumorigenetic and histomorphological differences between IBD-associated CRC and non-IBD CRC, suggesting differences in tumor behavior and response to treatment. We aimed to compare tumor recurrence and survival rates following postoperative chemotherapy in CRC patients with and without IBD. Methods: Search of the Cleveland Clinic's CRC database revealed 65 patients who had IBD-associated CRC and received postoperative adjuvant chemotherapy between 1994 and 2010. Twenty-one patients were excluded due to incomplete clinical data. Propensity score-matching based on age, surgery intent, CRC site, tumor grade, American Joint Committee on Cancer (AJCC) stage and T stage was used to match IBD and non-IBD patients (1:4). Competing risk and Cox regression models were used to analyze differences in disease-free survival and overall survival, respectively. Results: Forty-four patients with IBD-associated CRC were matched to 176 patients with non-IBD CRC. Among IBD patients, 29 (66%) had ulcerative colitis, 14 (32%) had Crohn's disease, and one (2%) had indeterminate colitis. Mean IBD diagnosis age was 28.1 ± 14.5 years, and mean IBD duration at time of CRC treatment was 21.5 ± 12.6 years. Ten (23%) IBD patients had tumor recurrence compared with 34 (19%) non-IBD patients ( P = .074). There was no significant difference in disease-free survival (hazard ratio [HR] = 0.60; 95% CI: 0.35–1.05; P = 0.074) or overall survival (HR = 0.87; 95% CI: 0.54–1.4; P = 0.58) between IBD and non-IBD patients. Conclusion: Patients with IBD-associated CRC have comparable rates of tumor recurrence and survival following postoperative chemotherapy as CRC patients without IBD. Prospective studies are needed to confirm these findings and guide therapeutic decisions.